2017
DOI: 10.1016/j.aninu.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Responses of milk production of dairy cows to jugular infusions of a mixture of essential amino acids with or without exclusion leucine or arginine

Abstract: The purpose of this study was to determine effects of jugular infusion of either balanced or imbalanced amino acid mixture on milk production and composition in dairy cows. Eight mid-lactation Holstein cows were randomly assigned to 5-d continuous jugular infusions of saline (CTL), essential amino acid (EAA) mixture prepared on the profile of casein (CSN, 160 g/d), EAA mixture excluding leucine (Leu) (−Leu, 163 g/d) or EAA mixture excluding arginine (Arg) (−Arg, 158 g/d) in a duplicated 4 × 4 Latin square desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Clark et al (1975) found that arginine uptake by the mammary gland associated with milk yield in rabbits and cows; however, O'Quinn et al (2002) revealed that the rate of arginine catabolism in the lactating sows was greater than that for the pregnant or non-lactating sows. Furthermore, Tian et al (2017) stated that arginine deficiencies had negative effects on milk yield and milk protein yield. The investigators attributed the effect of arginine to its crucial role in regulating protein turnover in mammary epithelial cells by activating the mechanistic target of the rapamycin (mTOR) cell signaling pathway (Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Clark et al (1975) found that arginine uptake by the mammary gland associated with milk yield in rabbits and cows; however, O'Quinn et al (2002) revealed that the rate of arginine catabolism in the lactating sows was greater than that for the pregnant or non-lactating sows. Furthermore, Tian et al (2017) stated that arginine deficiencies had negative effects on milk yield and milk protein yield. The investigators attributed the effect of arginine to its crucial role in regulating protein turnover in mammary epithelial cells by activating the mechanistic target of the rapamycin (mTOR) cell signaling pathway (Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Dairy products have an important role in human healthy life because of the abundant nutrients and active substances. Milk protein and milk fat are important components of milk that affect dairy industry competitiveness (Tian et al 2017). Mastitis is the most frequent and important disease in dairy cattle worldwide causing great economic losses to the dairy industry.…”
mentioning
confidence: 99%
“…The significantly decreased FSR for −BCAA while being not affected by −Leu highlights that the other BCAA, Ile, and Val alone or together with Leu could stimulate lactose synthesis independent of glucose uptake. In order for evaluating further the responses for BCAA deficiencies, we performed a meta-analysis (unpublished data) using the methodology described in Appuhamy et al (2013) and data from in vivo studies published in Korhonen et al (2002), Haque et al (2012), andTian et al (2017). In those studies, lactose yields of dairy cows were measured in response to abomasal or intravenous infusions of a complete EAA mixture or the EAA mixtures devoid of individual BCAA.…”
Section: Effects Of Bcaa On Lactose Synthesis Rates In Mtsmentioning
confidence: 99%